Clinical Outcomes in Preterm Infants Following Institution of a Delayed Umbilical Cord Clamping Practice Change. (June 2018) - Fenton, Christen; McNinch, Neil L; Bieda, Amy; Dowling, Donna; Damato, Elizabeth
Abstract : Background: Evidence supports a significant reduction in the incidence of intraventricular hemorrhage (IVH) in preterm infants receiving delayed umbilical cord clamping (DCC). Purpose: This study evaluated clinical feasibility, efficacy, and safety outcomes in preterm infants (<36 weeks' gestational age) who received DCC following a practice change implementation intended to reduce the incidence of IVH. Methods: Infants receiving DCC (45-60 seconds) were compared with a sample of infants receiving immediate umbilical cord clamping (<15 seconds) in a retrospective chart review (N = 354). The primary outcome measure was the prevalence of IVH. Secondary safety outcome measures of 1- and 5-minute Apgar scores, axillary temperature on neonatal intensive care unit admission, and initial 24-hour bilirubin level were also evaluated. Gestational age was examined for its effect on outcomes. Results: Although the small number of infants with IVH precluded the ability to detect statistical significance, our raw data suggest DCC is efficacious in reducing the risk for IVH. For infants 29 or less weeks' gestational age, admission axillary temperature was significantly higher in those who received DCC. No differences were found in 1- and 5-minute Apgar scores, 24-hour bilirubin level, or hematocrit level between the two groups. Infants more than 29 weeks' gestational age who received DCC had significantly higher 1-minute Apgar scores, temperature, and 24-hour bilirubin level. Implications for Practice: Clinicians should advocate for the implementation of DCC as part of the resuscitative process for preterm neonates. Implications for Research: Future studies are needed to evaluate the effect of DCC on other clinical outcomes and to investigate umbilical cord milking as an alternative approach to DCC.